Priority hierarchies in subject assignment in English: case of conflation - Rodríguez Juárez, Carolina (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2005)
The theoretical model of Functional (Discourse) Grammar initially developed by Simón C. Dik (1997a/b) stresses the relevance of implicational hierarchies in grammatical operations and claims that these hierarchies, although they present individual properties associated with intrinsic, functional and hierarchical constraints, may interact with each other to the extent that some of them could be grouped and reformulated as a single hierarchy gathering properties of different nature. In this paper, we will explore these cases of conflation within the domain of the grammatical operation of Subject assignment in one particular language, viz. English, and will suggest new cases of overlap between some of these priority features which might be appropriate in a descriptive approach to Subject selection in the English language.